İŞ ADAMLARININ KİŞİLİK ÖZELLİKLERİNİN GİRİŞİMCİLİK POTANSİYELİ ÜZERİNDEKİ ETKİSİ: ELAZIĞ İLİNDE BİR UYGULAMA - GÖÇER, ABDULLAH (Fırat Üniveristesi, 2021)
Günümüzde ekonominin gelişiminde girişimcilik anahtar rol olarak görülmekte ve ekonominin gelişebilmesi için girişimcilere duyulan ihtiyaç artmaktadır. Ekonomik olarak gereksinimleri ve eksiklikleri görüp, bunları fırsata çevirip, kar elde edebilen, yeni istihdam alanları oluşturabilen bireyler girişimci bireylerdir. Özellikle gelişmekte olan ülkeler için ekonomik olarak gelişmenin hızlandırılması, çalışma hayatında inovasyonun sağlanabilmesi ve günümüz koşullarında gelişmekte olan ülkelerin en büyük sorunu olan işsizlik gibi sorunların çözülmesi için girişimcilere ihtiyaç duyulmaktadır. Ancak girişimci kişilerin de ortaya çıkması ya da bireylerin girişimcilik potansiyelinin artması için bazı destekler gerekmektedir. Bireylerin girişimcilik potansiyelinde girişimci kişilik özelliklerinin etkisi bulunmaktadır. Kişilik özelliklerini ise aile yaşamı ve sosyal ilişkileri etkilemektedir. Bu durumda kişilik özelliklerinin, girişimcilik potansiyeline etki ettiği söylenebilir. Tez çalışmasının amacı, girişimci kişilik özelliklerinin girişimcilik potansiyeline etkilerini incelemektir. Konunun seçilme amacı girişimciliğin ülke ekonomisine sağladığı ya da sağlayabileceği katkının önemidir. Çalışmanın amacına ulaşabilmek için Elazığ ilinde Elazığ Ticaret ve Sanayi Odası ile görüşülmüş ve yüksek ciroya sahip işletmelerle ilgili bilgi alınmıştır. Bilgi alınan işletmelerin yöneticilerine kişilik özelliklerinin girişimcilik potansiyeline etkisini ölçebilmek amacıyla anket uygulanmıştır. Uygulanan anket ile kişilik özelliklerinin kişinin girişimcilik potansiyeli üzerindeki etkisi belirlenmeye çalışılmıştır. Anahtar Kelimeler: Girişim, Girişimci, Girişimcilik, Kişilik, Kişilik Özellikleri, Girişimci Kişilik, Girişimci Kişilik Özellikleri

Today, entrepreneurship is seen as a key role in the development of the economy and the need for entrepreneurs is increasing for the development of the economy. Individuals who can see the economic needs and deficiencies, turn them into opportunities, generate profits, and create new employment areas are entrepreneurial individuals. Entrepreneurs are needed, especially for developing countries, to accelerate economic development, to ensure innovation in working life, and to solve problems such as unemployment, which is the biggest problem of developing countries in today's conditions. However, some support is required for the emergence of entrepreneurial people or for increasing the entrepreneurial potential of individuals. Entrepreneurial personality traits have an effect on the entrepreneurial potential of individuals. Personality traits affect family life and social relations. In this case, it can be said that personality traits affect entrepreneurship potential. The aim of the thesis is to examine the effects of entrepreneurial personality traits on entrepreneurial potential. The purpose of choosing the subject is the importance of the contribution that entrepreneurship provides or can provide to the country's economy. In order to reach the aim of the study, Elazig Chamber of Commerce and Industry was contacted and information was obtained about businesses with high turnover in Elazig. In order to measure the effect of personality traits on entrepreneurial potential, a questionnaire was applied to the managers of the enterprises from which information was obtained. With the applied questionnaire, the effect of personality traits on the entrepreneurial potential of the person was tried to be determined. Keywords: Entrepreneurship, Entrepreneur, Entrepreneurship, Personality, Personality Traits, Entrepreneurial Personality, Entrepreneurial Personality Traits
Abstract the effect of business people's characteristics on potential of entrepreneurship: A case study in Elazig
Keywords: Ekonomi